Using the Myers-Briggs Personality Type Indicator to Strengthen Extension Programs - Alexa J. Lamm; Ricky W. Telg (EDIS, 2015)
A person’s personality affects the way he or she learns best. Extension programs can use an understanding of different learning styles and preferences to reach the greatest number of people. This EDIS document is the second in the Teaching to Different Personality Types series, and covers the Myers-Briggs Type Indicator (MBTI®). Written by Alexa J. Lamm and Ricky W. Telg, and published by the UF Department of Agricultural Education and Communication, September 2015. (Photo credit: Rawpixel Ltd/iStock/Thinkstock.com)